Efficient wireless power transfer for a moving electric vehicle by digital control of frequency - Yamaguchi, Kazuya; Okamura, Ryusei; Yian Kiat, Adrian Wee; Iida, Kenichi (Institute of Advanced Engineering and Science, 2024)
Recently, demand for electric vehicles has been increasing as a countermeasure against global warming, but they currently face many problems compared to gasoline-powered vehicles. For example, charging takes time, and there are few places where electric vehicles can be charged. If AC power supplies that can transfer energy to electric vehicles wirelessly exist under the lanes where electric vehicles drive, the cruising range will be increased. In this study, assuming wireless power transfer to a moving electric vehicle, an experiment was conducted to light up a light-emitting diode (LED) on a moving electric model car. To improve the efficiency of transfer, the optimal frequency for the position of the electric model car was calculated, and the value was fed back to the power supply to adjust the frequency in real time.